1973
DOI: 10.1136/bjo.57.8.566
|View full text |Cite
|
Sign up to set email alerts
|

Lattice degeneration in a family: with retinal detachment and cataract.

Abstract: Nearly a century ago Lang (i 885) described the occurrence of retinal detachment in a brother and his sister. Since that time many pedigrees have been presented to illustrate the hereditary nature of some cases of simple (syn. serous, idiopathic, rhegmatogenous, perforated) retinal detachment. Most of the earlier authors related the occurrence of the detachment to the presence and degree of co-existing myopia. Braendstrup (i94I) and Cuendet, Streiff, and Dufour (1958) have described a myopic family of five ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Former reports regarding familial, nonsyndromic RRD predominantly describe myopic families. 18,23,24,28,32 The genetic background of myopia is still unclear, but linkage in specific families has been found with 5 different loci (Xq28; 18p11.31; 12q21-q23; 7q36; 17q21-q22). 19,[33][34][35][36] Cataract extractions did not precede RRD considerably more frequently in relatives of cases than in relatives of controls, indicating that cataract extraction did not explain familial aggregation of RRD in our study.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Former reports regarding familial, nonsyndromic RRD predominantly describe myopic families. 18,23,24,28,32 The genetic background of myopia is still unclear, but linkage in specific families has been found with 5 different loci (Xq28; 18p11.31; 12q21-q23; 7q36; 17q21-q22). 19,[33][34][35][36] Cataract extractions did not precede RRD considerably more frequently in relatives of cases than in relatives of controls, indicating that cataract extraction did not explain familial aggregation of RRD in our study.…”
Section: Commentmentioning
confidence: 99%
“…Case reports and twin studies have shown that retinal dialysis, idiopathic giant tears, lattice degeneration, and myopia can aggregate in families or can show a remarkable resemblance among relatives. [13][14][15][16][17][18] The genetic risk for myopia has been studied most profoundly, and a fifth genetic locus for high myopia was found recently. 19 Multiple RRDs, both with and without myopia, have been described in families.…”
mentioning
confidence: 99%
“…Previously, autosomal-dominant inheri tance with reduced penetrance or autoso mal-recessive inheritance has been postu lated for the genetics of lattice degeneration of the retina, but the view was based on pedigree analysis of a single 'interesting' family or on a clinical impression [2][3][4][5], Since lattice degeneration of the retina is found frequently, it may occur often that the transmission pattern is apparently matched to the autosomal-dominant or recessive mode of inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk for retinal de-tachment is considerably low with reference to the relatively high prevalence, lattice de generation may be the most important among a variety of peripheral retinal anom alies which potentially induce retinal break, and in fact, it is responsible for about 30-40% of patients with rhegmatogenous retinal detachment [1], In view of the devel opmental or degenerative process of its reti nal pathology, it is possible to assume a hereditary factor in the genesis of this con dition. Pedigrees with more than 2 affected family members with or without associated retinal detachment have been described, and on the basis of pedigree analysis either auto somal-dominant or recessive inheritance has been suggested [2][3][4][5], There has, how ever, been no previous study dealing with data accumulated from many families, and this may be the reason for yet inconclusive views concerning the genetics of lattice de generation of the retina. This paper describes a preliminary genet ic-statistical analysis of our observation with particular interest in the first-degree rela tives of patients.…”
mentioning
confidence: 99%